First Component of Complement and Thrombosis - Wautier, J L; Ollier-Hartmann, M P; Kadeva, H; Cohen, F; Hartmann, L; Caen, J P (Thrombosis and Haemostasis, 1981)
The previous demonstration of an association between the collagen-like region of Clq (subcomponent of the first component of complement) and human platelets and of the inhibitory properties of C1q on platelet adhesion and aggregation to or by collagen has led us to consider the first component of complement as a possible modulator of the platelet-collagen interaction. Since collagen represents a major component of the vessel wall, the modification of Cl could play a role in the development of thrombosis.We have therefore studied two patients with abnormalities of complement (low or undetectable C1, C4, C2 and deficiency in C1 inhibitor) who presented with acquired angioneurotic oedema. Both patients had a history of multiple episodes of arterial and/or venous thrombosis.Platelet associated C1q was decreased or undetectable, and this condition was associated with a specific increase of collagen induced aggregation thereby suggesting a possible mechanism for the recurrent thromboembolic episodes.
Keywords: Complement; Platelet aggregation; Collagen; Thrombosis; Angioneurotic oedema